Unicystic ameloblastoma of the mandible clinical case presentation and literature review - De la Paz López, Almallely; Recendez Santillán, Norith; Varela Ibáñez, Eduardo; Escamilla-Acosta, Marco A.; Romo-Hernández, Georgina (Mexican Journal of Medical Research ICSA, 2014)
Ameloblastoma is a neoplastic lesion that in its early stages does not present signs or symptoms; ages more common in which occurs this lesion are between 20 to 30 years of age, it has no predilection by any gender; their formation can be derived epithelial involved with the formation of teeth. The objective of this review is to present a clinical case of a 14-year-old male patient referral to the Hospital del Niño DIF Hidalgo, which presented volume increased in right hemiarch, diagnostic studies were conducted in which the result was an Unicystic Ameloblastoma of the Mandible, which was addressed through conservative treatment. It is intended that this review will update the knowledge and therapeutic approaches to this disease, assessing tumor location and patient age.